Application of Digital Anti-Coincidence Counting Method for Primary Activity Determination of 59Fe - A. Agusbudiman; K.B. Lee; J.M. Lee (PPIKSN-BATAN, 2019)
As a radiopharmaceutical, the use of 59Fe is classified as a high pharmaceutical risk product. Therefore, a standard reference for activity measurement of 59Fe is necessary to ensure its metrological aspect. This paper describes an alternative method for primary activity determination of 59Fe for establishing a standard reference. The 59Fe solution was prepared using two different cocktails and measured by the 4pb(LS)-g counting system using a digital anti-coincidence counting method with emulated live-time of the extending dead-time. A final activity results at the reference time for the two samples series are (473.32± 2.55) kBq/g and (477.14 ± 2.42) kBq/g with quoted uncertainty evaluated at k = 1. The final activity was compared to the value obtained from the other two coincidence counting method and found to be in a good agreement within its uncertainty value.